Assessing The Readiness Of Malaysian For The New Economy: A Case Study In The Selangor Area - Ling, Tan Mei (2001)
The main objective of this study is to assess the readiness of Malaysians for the New Economy, with a focus in the Selangor State. It is also the objective of the study to identify factors that contribute to the readiness for the New Economy.